Evaluation of aroma in Malaysian rice landraces through sensory test and molecular method approach - Site Noorzuraini binti Abd Rahman; Rosimah Nulit; Faridah Qamaruz Zaman; Khairun Hisam Nasir; Mohd Shahril Firdaus Ab Razak; Mohd Ramdzan Othman; Nur Idayu Abd Rahim; Nor Sufiah Sebaweh (Journal of Animal and Plant Sciences, 2024)
Aroma is one of the major important grain quality traits that play a significant role in consumer preferences. In Malaysia, consumers have shown a marked preference for high-quality rice types. Thus, it is essential to identify rice landraces with aroma for promotion as potential donors for the development of high-quality rice to meet consumer demand and reduce dependency on imported high-quality rice types. The aroma of 30 rice landraces was determined using sensory tests and molecular markers. The presence of aroma in cooked rice was determined through nose sensory evaluation by five panelists. Molecular analysis was performed using two aroma-specific primers, FMbadh2-E7 and Badex7-5. The sensory test revealed that only five rice landraces had a strong aroma; whereas eleven had a slight aroma. FMbadh2-E7 was found to have the most alleles (6) with a major allele frequency of 0.53. Whereas, Badex7-5, has a major allele frequency of 0.51, with 5 alleles detected at the locus. The dendrogram for aroma was generated by UPGMA cluster analysis using two SSR primers, which separated the rice landraces into two distinct clusters; Cluster 1 consists of fifteen rice landraces with non-aroma standards, while Cluster 2 consists of fifteen rice landraces with aroma standards. The identified rice landraces with aroma based on the two methods, namely Kenawit, Gertok, Pandan, Nangka, Tiga Bulan, Lumpur, Grik, Sanguo Pandan, Kurau, Bidor, and Wangi, can be promoted in breeding programs as potential donors.
Keywords: aromatic rice; 2-acetyl-1-pyrroline; specialty rice; Oryza sativa; SSR primers